Semantic interactions in the Internet of Things. (30th July 2013) - Estrada–Martinez, Paul E.; Garcia–Macias, J. Antonio
The long–term vision of the Internet of Things (IoT) is to extend the reach of the internet to any object we can imagine. This new level of connectivity and the presence of smart objects in our environments will make possible systems and applications requiring new kind of interactions. In this paper, we present our proposal of semantic interactions for addressing interaction problems in the IoT. We describe some possible scenarios of the IoT where users interact with smart objects in smart spaces. We explain how semantic web technologies can be used for creating richer interactions and also present the evaluation of our proposal by applying the concepts of this work in a system prototype.